Tetrapropyl-tetraphenyl-diindenoperylene derivative as a green absorber for high-voltage stable organic solar cells - Meiss, J; Hermenau, M; Tress, W; Schuenemann, C; Selzer, F; Hummert, M; Alex, J; Lackner, G; Leo, K; Riede, M (American Physical Society, 2011)
We present small molecule organic solar cells (SMOSC) based on flat heterojunctions (FHJ) of the alternative green donor 2,3,10,11-tetrapropyl-1,4, 9,12-tetraphenyl-diindeno[1,2,3-cd:1′,2′,3′-lm]perylene (P4-Ph4-DIP) and the fullerene C60. P4-Ph4-DIP absorbs in the green spectral range and thus fills the spectral gap that standard absorber materials (zinc or copper phthalocyanine for red and C60 for blue absorption) leave, thus allowing broad coverage of the sun spectrum, which is of major interest for tandem devices. The materials properties of P4-Ph4-DIP are studied, and SMOSC are characterized by current voltage, external quantum efficiency, and aging measurements. The solar cells display very high fill factors FF > 76% and open circuit voltages VOC of close to 1 V. Mismatch-corrected efficiencies of up to 1.9% are obtained. Aging measurements show that C60 in conjunction with P4-Ph4-DIP yields extremely stable devices. We observe ≈ 88% of the initial efficiency after 2500 h illumination at 999 mW/cm2 illumination intensity, with no observable change in short-circuit current density. Furthermore, we also show that a systematic variation of donor thickness in FHJ can be combined with transfer matrix formalism-based optical simulations and the continuity equation for excitons to reliably determine the exciton diffusion length LD. A value of 9 ± 1 nm is found for P4-Ph4-DIP. © 2011 American Physical Society.